QUALITY ANALYSIS OF CATFISH FILLET (Pangasuius hypophthalmus) SALTED WITH DIFFERENT SALT LEVELS DURING THE STORAGE ROOM TEMPERATURE - Nurkadri Lubis; Sukirno Mus; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in December 2014 at the Faculty of Fisheries andMarine Science at the University Riau. The purpose of this research is to observe the levelssalt which have been applied to the fillet of catfish (Pangasius hypophthalmus) theobservation which also involved the storage time in room temperature. The methodologyused in the research was the experiment research which compare the salt level of 15% and30% in order to see the best quality after using the interfal time of observation end of 7 and21 days. The quality parameters used are the proximate value such as water content, protein,fat and Staphylococcus aureus bacteria. The result showed that the different salt levels basedon the parameters about do give a significant difference, salinity that can maintain the qualityof salted fish fillets until the end of the storage is salt content of 30% is the volue of watercontent 8,77%, 23,99 protein content, fat content of 5,20% and not found of bacteriaStaphylococcus aureus.Keywords: Catfish, fillet, salt, storage